Implementasi Sistem Among Dalam Manajemen Kepemimpinan Kepala Sekolah Sebagai Upaya Mewujudkan Sekolah Ramah Anak Di Smp Negeri 1 Seyegan (Universitas Sarjanawiyata Tamansiswa, 2025)
The research objectives include: (1) To understand the principal's management in realizing a Child-Friendly School at SMP Negeri 1 Seyegan. (2) To understand the implementation of Ki Hajar Dewantara's Among system in the principal's leadership in realizing a Child-Friendly School at SMP Negeri 1 Seyegan. (3) To identify the obstacles or challenges faced by the principal in realizing a Child-Friendly School at SMP Negeri 1 Seyegan. (4) To understand the strategies implemented by the principal in realizing a Child-Friendly School at SMP Negeri 1 Seyegan.The type of research used is qualitative research, employing techniques such as interviews, observations, and documentation. In this study, the researcher will explore and discover how the Among system is implemented in the school principal's leadership management as an effort to realize a Child-Friendly School at SMP Negeri 1 Seyegan. The analysis used is the Miles and Huberman model. The researcher reduces, presents, draws conclusions, and verifies the data. Based on the results of the data analysis, the following conclusions were drawn: (1) Leadership management in realizing a Child-Friendly School has been well implemented by the principal through planning, organizing, executing, and supervising the implementation of Child-Friendly School activities. (2) The Among System has been implemented by the principal by involving school members in planning, organizing, mobilizing, and supervising Child-Friendly School activities. (3) The obstacles in realizing a Child-Friendly School at SMP Negeri 1 Seyegan can be overcome through communication and involvement of all internal and external parties, resulting in a safe and comfortable school for students and educators. This can be seen from the absence of violence and bullying at SMP Negeri 1 Seyegan, creating a safe and comfortable environment for students and educators, allowing the teaching and learning activities to proceed well. (4) Effective communication has been implemented by the principal with parents/guardians at SMP Negeri 1 Seyegan as a strategy to enhance supervision of students to prevent violence and bullying.